Neck Exercises Compared to Muscle Activation During Aerial Combat Maneuvers - Netto, Kevin; Burnett, Angus; Coleman, J. (Aerospace Medical Association, 2007)
INTRODUCTION: Performing specific neck strengthening exercises has been proposed to decrease the incidence of neck injury and pain in high performance combat pilots. However, there is little known about these exercises in comparison to the demands on the neck musculature in flight.METHODS: Eight male non-pilots performed specific neck exercises using two different modalities (elastic band and resistance machine) at six different intensities in flexion, extension, and lateral bending. Six Royal Australian Air Force Hawk pilots flew a sortie that included combinations of three +Gz levels and four head positions. Surface electromyography (EMG) from selected neck and shoulder muscles was recorded in both activities.RESULTS: Muscle activation levels recorded during the three elastic band exercises were similar to in-flight EMG collected at +1 Gz (15% MVIC). EMG levels elicited during the 50% resistance machine exercises were between the +3 Gz (9-40% MVIC) and +5 Gz (16-53% MVIC) ranges of muscle activations in most muscles. EMG recorded during 70% and 90% resistance machine exercises were generally higher than in-flight EMG at +5 Gz.DISCUSSION: Elastic band exercises could possibly be useful to pilots who fly low +Gz missions while 50% resistance machine mimicked neck loads experienced by combat pilots flying high +Gz ACM. The 70% and 90% resistance machine intensities are known to optimize maximal strength but should be administered with care because of the unknown spinal loads and diminished muscle force generating capacity after exercise.